Utilization of Artificial Intelligence Technology in Research: Perspective of the Value and Norms of Researchers - Nuha, Moch. Syihabudin; Diniyah, Usrotun; Taneo, Mario Martin; Hidayah, Nur; Hotifah, Yuliati (The Indonesian Institute of Science and Technology Research, 2024)
The era of the industrial revolution has entered its peak in 5.0 which is an era where humans coexist full of technology. One of them is artificial intelligence and the products it produces such as ChatGPT, OpenAI, and artificial intelligence in other fields. In this era, humans will be given all kinds of conveniences from technology. The search for truth can be done quickly but less accurately. Artificial intelligence uses big data that will continue to be filled with various knowledge so that in the end intelligence can be utilized properly. The use of artificial intelligence technology in research conducted by researchers should still follow the rules, values, and norms in research. Values and norms in research will lead researchers to be open, fair, responsible, and skeptical of research results. The research method used is a literature study conducted by finding literature sources, reading literature, selecting literature, and analyzing related literature utilizing artificial intelligence in research. The purpose of this study is to find values and norms in research that uses artificial intelligence technology. The result of this study is that a researcher must have the value of objectivity, honesty, fairness, responsibility, stewardship, and openness and continue to develop skepticism, responsibility, ease of understanding, and critical thinking behavior that researchers must have. There are advantages and disadvantages to the use of artificial intelligence in research. The advantages include reference management, search for reference sources, plagiarism checking, and discussions between researchers. While the drawback is the critical thinking ability of researchers, plagiarism, fabrication, and falsification of research data. For this reason, good and responsible researchers must follow the values, values, and norms in research. Researchers must be responsible for the results of their research because the results of their research are a source of knowledge and will be read by readers widely.